Angiotensin (1-7) Decreases Myostatin-Induced Nf-Kb Signaling and Skeletal Muscle Atrophy - Gonzalez-Rojas, A; Cabello-Verrugio, C; Abrigo, J (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Myostatin is a myokine that regulates muscle function and mass, producing muscle atrophy. Myostatin induces the degradation of myofibrillar proteins, such as myosin heavy chain or troponin. The main pathway that mediates protein degradation during muscle atrophy is the ubiquitin proteasome system, by increasing the expression of atrogin-1 and MuRF-1. In addition, myostatin activates the NF-kB signaling pathway. Renin–angiotensin system (RAS) also regulates muscle mass. Angiotensin (1-7) (Ang-(1-7)) has anti-atrophic properties in skeletal muscle. In this paper, we evaluated the effect of Ang-(1-7) on muscle atrophy and signaling induced by myostatin. The results show that Ang-(1-7) prevented the decrease of the myotube diameter and myofibrillar protein levels induced by myostatin. Ang-(1-7) also abolished the increase of myostatin-induced reactive oxygen species production, atrogin-1, MuRF-1, and TNF-α gene expressions and NF-kB signaling activation. Ang-(1-7) inhibited the activity mediated by myostatin through Mas receptor, as is demonstrated by the loss of all Ang-(1-7)-induced effects when the Mas receptor antagonist A779 was used. Our results show that the effects of Ang-(1-7) on the myostatin-dependent muscle atrophy and signaling are blocked by MK-2206, an inhibitor of Akt/PKB. Together, these data indicate that Ang-(1-7) inhibited muscle atrophy and signaling induced by myostatin through a mechanism dependent on Mas receptor and Akt/PKB. © 2020 by the authors. Licensee MDPI, Basel, Switzerland. T.